Disclosing monetary policy - Mayer, Thomas ([New York] : Salmon Brothers Center for the Study of Financial Institutions, Graduate School of Business Administration, New York University, 1987)
This revised monograph contains a monetary policy reports about federal reserve or fed. The revision examine policy and activities of fed in the second half of 1982.
Bibliography: p. 70-72.
asm 14/02/19
Loans
Keywords: Monetary policy; Government information